On the rocks [videorecording (DVD)] - Coppola, Sofia, 1971-; Coppola, Sofia, 1971-; Coppola, Sofia, 1971-; Jones, Rashida; Murray, Bill, 1950 September 21-; Wayans, Marlon (Lionsgate, 2021)
A mother of two young daughters starts having doubts about her husband's fidelity and confides about her suspicions to her playboy father, who proposes an investigation into the matter.